Silagem de coproduto do maracujá com fubá de milho para ovinos - Simioni, Tiago Adriano (2015)
This study aimed to evaluate the effects of adding cornmeal (0, 10 and 20%) in silage of passion and co-product level (10 to 30%) used in the diet of sheep partially substituting hay on consumption and total digestibility of nutrients and the energy value of the experimental diets. We used twelve male sheep, approximately 36.5 ± 2.1 kg crossbred Santa Inês, divided in six Latin squares 2 x 2. The dry matter (DM kg day-1 kg-1 and PV0,75) organic matter (OM), crude protein (CP) and ether extract (EE) were not affected (P <0.05) by the type of silage included in the diet passion fruit byproduct. However, the EE consumption (kg day-1) differ depending on the inclusion levels in silage passion coproduct (P <0.05). It was observed effect of interaction between the cornmeal level in silage of passion fruit co-product and the percentage inclusion in the diet (P <0.05). The inclusion level of 30% of passion fruit silage in the diets provided higher consumption of EE (P <0.05) compared to those containing 10%. The silage of passion fruit byproduct present EE concentration, 7.98, 7.53 and 6.17% DM, with cornmeal inclusion levels of 0, 10 and 20% respectively, and the seed component of this coproduct more contributed to the variations in the concentration of EE. The energy content of the diets was not affected by the level of inclusion of silage in the diet and the level of cornmeal in the silages (P <0.05). Thus, passion fruit byproduct of silages with up to 20% inclusion of cornmeal were characterized showing an average 75% TDN, could be an alternative for inclusion in diets of ruminants as a substitute for bulky or concentrated energy food